Determination of a nox and soot emission occurring during the operation of an internal combustion engine - WENZEL SEBASTIAN; SCHUMACHER HERBERT (2013)
In order to very accurately ascertain the pollutant emission of the motor vehicle, which occurs during the operation of an internal combustion engine, without the use of complex measurement and test engineering, it is proposed, that during the operation of the internal combustion engine at least one cylinder pressure is in each case acquired at specifiable crankshaft angles, scanning values of a heating rate assigned to the acquired cylinder pressures are determined, the scanning values of the heating rate are provided to a specifiable model as input values, a crankshaft angle assigned to the initiation of combustion, an air/fuel ratio and an exhaust gas recirculation rate are ascertained and provided to the model as input values and the pollutant emission is determined as a function of the input values using the model.